Innovation farm: Teaching artificial intelligence through gamified social entrepreneurship in an introductory MIS course*. (5th August 2021) - Chen, Yu; Albert, Leslie Jordan; Jensen, Scott
ABSTRACT: In the past few years, an increased use of artificial intelligence (AI) by businesses across a range of industries has led to greater demand for employees with AI skills. This raises the question of how educators can introduce AI technologies to undergraduate business students while also developing their higher‐order thinking skills and preparing them for the complex challenges facing today's business leaders. At the same time, we have also witnessed a growing interest in social entrepreneurship among our student population. To address both needs, we designed and implemented the "Innovation Farm, " a gamified social entrepreneurship startup project, to help students learn the concepts and applications of AI in an introductory management information systems (MIS) course. The students work in teams to propose AI‐powered products and services targeting real‐world social issues. The project cultivates social awareness and empathy in students, fosters innovation, and introduces them to current AI technologies while also reinforcing their understanding of MIS course content. Students found the gamified approach engaging, as they are tackling real‐world social issues while also learning about innovation, collaboration, branding, and fundraising for a social startup. Students reported positive outcomes related to innovating using technology, making an impact through real‐world projects, and practicing their teamwork and leadership skills.